2019
DOI: 10.25186/cs.v14i1.1529
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Coffee Progenies With Large Beans Resistant to Rust and Cercospora Leaf Spot

Abstract: <p>Rust is the main disease of coffee. Recently, cercospora leaf spot has grown in importance, intensifying defoliation and decreasing grain yield. The aim of this study was to use a mixed model approach to select the best progenies of "Big Coffee VL" for resistance to rust and cercospora leaf spot. We used 12 progenies with high bean yields. Based on bean size, leaves and plant size, plants within each progeny were classified as "small" (P), "medium" (M) and "large" (G). The experimental design was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…Recent studies have shown genetic variability between "Big Coffee VL" progenies, regarding disease resistance, bean size, yield, besides physiological and anatomical characteristics (Castanheira et al, 2016;Pereira et al, 2019;Silva, 2016). In this study, it is possible to observe this variability among the progenies through graphic dispersion, shown in Figures 3 and 4, which was similar to the grouping by Tocher's optimization method.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have shown genetic variability between "Big Coffee VL" progenies, regarding disease resistance, bean size, yield, besides physiological and anatomical characteristics (Castanheira et al, 2016;Pereira et al, 2019;Silva, 2016). In this study, it is possible to observe this variability among the progenies through graphic dispersion, shown in Figures 3 and 4, which was similar to the grouping by Tocher's optimization method.…”
Section: Discussionsupporting
confidence: 79%
“…Regarding physical quality, the results found in this study corroborate a study carried out by Krohling et al (2018) who evaluated the adaptation of arabica coffee cultivars in the mountain region of Espírito Santo, Brazil, observing differences as a function of grain size. In this way, it is possible to select genotypes with greater uniformity of grain size, and higher percentages of chato graúdo sieves (Pereira et al, 2013;Rodrigues et al, 2014;Cardoso et al, 2016), having in view of the fact that obtaining coffee beans from high sieves can promote greater aggregation of value to the product, in addition to being related to greater productivity and appreciation of the product in the international market (Pereira et al, 2013;Borém et al, 2020). In a study carried out with progenies from the crossing of Catuaí and Icatu cultivars and descendants of Híbrido de Timor, the progenies that presented the highest averages for the sieve characteristic "17 and above" were those that also presented higher productivity (Pinto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…comercial 'Sarchimor MG 8840' presenta resistencia a la enfermedad, seguida de otros genotipos de la colección Sarchimor, seguida de individuos de la colección de germoplasma (Botelho et al, 2017). Otras fuentes de resistencia son las reportadas por Pereira et al (2019), quienes describen al cultivar 'Big Coffee VL' por presentar características de grano largo, y sus progenies 'M5' y 'P23' poseen buenas características de producción y un alto potencial de resistencia a C. coffeicola. Aunque se puede encontrar información sobre resistencia genética en café contra C. coffeicola, ésta aún no ha sido explorada a profundidad (Botelho et al, 2017).…”
Section: Manejo De La Enfermedadunclassified